2018
DOI: 10.1007/s00431-018-3245-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bilirubin in infants with hypoxic–ischemic encephalopathy

Abstract: Antioxidant properties of bilirubin have been reported in many studies. We hypothesized that bilirubin might be involved in neuroprotection mechanisms against oxidative stress in infants with hypoxic-ischemic encephalopathy (HIE) and that total serum bilirubin (TSB) might increase in these patients. We retrospectively studied infants with gestational age ≥ 35 weeks and birth weight ≥ 1800 g who were admitted to the neonatal intensive care unit (NICU) with a diagnosis of moderate-to-severe HIE and received or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
3
24
1
Order By: Relevance
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[63][64][65], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[63][64][65], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[62][63][64], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that colostrum exosomes increased the secretion of factors related to Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[68][69][70], leading to an increase in the risk factors that trigger inflammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [71][72][73].…”
Section: Exosomes Play a Key Role In Cell-to-cell Communication And Cmentioning
confidence: 93%